1994
DOI: 10.1111/j.1476-5381.1994.tb14775.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the tachykinin NK2 receptor in the human bronchus: influence of amastatin‐sensitive metabolic pathways

Abstract: 4 In the presence of amastatin the pseudopeptide MDL28,564 behaved as a partial agonist. 5 We conclude that the NK2 receptor subtype present in the human bronchus has properties similar to those described for the circular muscle of the human colon and thus may be classified as a 'NK2A' subtype. We show that the apparent potency of peptides, bearing N-terminal acidic residues, is influenced by an amastatin-sensitive peptidase, possibly aminopeptidase A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…An important finding of the present study is that the NK 2 receptor is the predominant if not the exclusive mediator of the excitatory effect of tachykinins in the smooth muscle of the human ureter. This is in keeping with the results of previous studies, performed on smooth muscles from the human urinary bladder (Maggi et al , 1988b; Dion et al , 1990), gastrointestinal (ileum, colon and oesophagus) (Maggi et al , 1989; Giuliani et al , 1991; Huber et al , 1993) and respiratory tract (Naline et al , 1989; Astolfi et al , 1994; Dion et al , 1990), although excitatory responses mediated by tachykinin NK 1 receptors have also been described in selected cases as the circular muscle of the human ileium (Zagorodnyuk et al , 1997) and small bronchi (Naline et al , 1996).…”
Section: Discussionsupporting
confidence: 90%
“…An important finding of the present study is that the NK 2 receptor is the predominant if not the exclusive mediator of the excitatory effect of tachykinins in the smooth muscle of the human ureter. This is in keeping with the results of previous studies, performed on smooth muscles from the human urinary bladder (Maggi et al , 1988b; Dion et al , 1990), gastrointestinal (ileum, colon and oesophagus) (Maggi et al , 1989; Giuliani et al , 1991; Huber et al , 1993) and respiratory tract (Naline et al , 1989; Astolfi et al , 1994; Dion et al , 1990), although excitatory responses mediated by tachykinin NK 1 receptors have also been described in selected cases as the circular muscle of the human ileium (Zagorodnyuk et al , 1997) and small bronchi (Naline et al , 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Tachykinin family members are prone to different levels of biodegradation by various endogenous placental peptidases, including neutral endopeptidase 24.11, angiotensin I-converting enzyme, bestatin-sensitive aminopeptidases, and amastatin-sensitive aminopeptidases (35)(36)(37)(38)(39)(40)(41)(42)(43). There is indirect evidence for specific patterns of tachykinin catabolism governed by the localized expression of these enzymes within human placenta tissue (44 -51).…”
Section: Discussionmentioning
confidence: 99%
“…Giuliani et al , (1993) found that the activities of linear peptide derivatives of NKA with an N‐terminal aspartyl residue were reduced by an amastatin‐sensitive peptidase. The estimated potency of [βAla 8 ]NKA(4–10) was significantly increased from a pD 2 value of 6.87 to 7.44 by amastatin (Astolfi et al , 1994).…”
Section: Discussionmentioning
confidence: 97%